Light Pollution in the Pohorje area (ali region) - Žiberna, Igor; Kisilak, Anja; Rajh, Mojca; Zagorc, Iztok; Hozjan, Žan (Journal for Geography, 2018)
Light pollution as a relatively new form of environmental pollution has been an increasing environmental problem since the 1980s. The source of light pollution in Slovenia is primarily public lighting along roads and cultural or sacral buildings, which are illuminated at night. In the article we were focused on the analysis of the state of light pollution in the Pohorje region, which mainly belongs to the protected area of ​​Natura 2000. We analyzed the situation on the basis of satellite data by considering the night spectral channel. We especially discussed the impact of night skiing in the Mariborsko Pohorje and Rogla ski resorts on the actual state of light pollution. Additionally, we evaluated the effect of selected illuminated buildings in the Pohorje region, which are habitats of bats, on the current state of light pollution in the direct vicinity of these facilities and in their surroundings.
Keywords: light pollution; night skiing; illuminated objects; remote sensing; geographical information system; Pohorj